PENGARUH HYPNOTHERAPY TERHADAP KEPATUHAN DIIT CAIRAN PADA PASIEN GAGAL GINJAL KRONIS RAWAT JALAN DI INSTALASI HEMODIALISA RS PKU MUHAMMADIYAH GOMBONG - Safitri -; Cokro Aminoto; Arnika Dwi Asti (LPPM UNIVERSITAS MUHAMMADIYAH GOMBONG, 2012)
Hypnotherapy is one of methods to send conviction for the patients. The method can be used to for patients who have no discipline in doing liquid diet. Objective: to determine the influence of hypnotherapy to the liquid diet compliance of chronic renal failure patients in Hemodialysis Installation of PKU Muhammadiyah Gombong Hospital. It is causal research using pre experiment with one group pre test and post test design. The research was done in Hemodialisys’s room RS PKU Muhammadiyah Gombong in 17 May to 17 June 2010. The samples of the study were 20 respondents based on the inclusion and exclusion criteria. The data were analyzed by using paired sample t-test with α=0. 05. The result of the research showed that there was insignificant influence of hypnotherapy to the liquid diet compliance of chronic renal failure patients in Hemodialysis Installation of PKU Muhammadiyah Gombong Hospital with t-count 0.811 (P=0.000). Hypnotherapy does not influence of hypnotherapy to the liquid diet compliance of chronic renal failure patients in Hemodialysis Installation of PKU Muhammadiyah Gombong Hospital. Keyword : hypnotherapy, discipline, liquid diet.